Protein Spesifik Cairan Kista Cysticercus bovis pada Sapi Bali yang Diinfeksi dengan Taenia saginata (SPECIFIC PROTEIN OF CYSTICERCUS BOVIS CYST FLUID ON BALI CATTLE EXPERIMENTALLY INFECTED WITH TAENIA SAGINATA) - Dharmawan, Nyoman Sadra; Dwinata, I Made; Swastika, Kadek; Damriyasa, I Made; Oka, Ida Bagus Made; Astawa, I Nyoman Mantik (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Cysticercus bovis is the larval stage of Taenia saginata, the bovine tapeworm. The infection of thislarval in cattle musculature causes Bovine cysticercosis or Cysticercosis bovis.  Bovine cysticercosis is foundworldwide, but mostly in developing countries, where unhygienic conditions, poor cattle managementpractices, and the absence of meat inspection are common.  The adult Taenia infection in man is referredto as taeniasis.  Taenia saginata taeniasis is also found almost all over the world.  The prevalence ofTaenia saginata taeniasis has reported up to 27.5% in Gianyar Bali. In order to control the diseases,vaccination against the larvae stages in cattle of Taenia saginata may play an important role in controllingthe disease in the endemic regions.  The aims of the present study were to prepare and to investigate theimmunogenic protein as vaccine candidate for controlling  Cysticercus bovis infection in in Bali cattle.Cysticercus protein from the cyst fluid was firstly used to immunize mice and the mice sera were thencollected. Cysticercus proteins then analyzed using sodium dodecyl sulfate-gel electrophoresis (SDS-PAGE).All cysticercus proteins were then visualized by Commasie blue staining. The proteins were also transferredonto nitrocellulose membrane and the immunogenic proteins were visualized by Western Blotting usingimmune sera raised in mice.  By Commasie blue staining, a total of 17 proteins were detected with themolecular weight of 14,86 kDa -122,40 kDa from the smallest to the largest. As many as 7 immunogenicproteins with the molecular weights of 16.81 kDa; 19.22 kDa; 20.98 kDa; 27.41 kDa; 34.02 kDa; 38.31 kDa;and 54.94kDa were detected.
Keywords: immunogenic, cyst fluid of Cysticercus bovis